PENGARUH GAYA KEPEMIMPINAN, PROFESIONALISME, LINGKUNGAN KERJA DAN KECERDASAN EMOSIONAL TERHADAP KINERJA PENGELOLA KEUANGAN (Studi Pada SKPD Kota Dumai) - Bobbie Windura; Raja Adri Satriawan; Sem Paulus Silalahi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to analyze the influence of leadership style, professionalism, work environment and emotional intelligence on the performance of financial managers in Kota Dumai. Sampling technique used is purposive sampling. Respondents in this study is the Head of Department, Financial Administration Officer, the Technical Activities Executive Officer and Treasurer Expenditure. The sample used in this study were 72 respondents. The statistical method used to test the hypothesis of the research is multiple linear regression analysis using SPSS software version 22.0. The results of the study found that leadership style variable influence on the performance of financial operators with a regression coefficient of 0.179, professionalism effect on the performance of financial operators with a regression coefficient of 0.216, the work environment influence on the performance of financial operators with a regression coefficient of 0.347, emotional intelligence affect the performance manager finance with a regression coefficient of 0.238). The result of the coefficient of determination (R2) of 0.610 means that the contribution of independent variable influence to variable by 61% and the remaining 39% are influenced by other variables.Keywords : Leadership Style, Professionalism, Work Environment, Emotional Intelligence and Performance